# z^7+2(z^4)+4z=0

## Simple and best practice solution for z^7+2(z^4)+4z=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for z^7+2(z^4)+4z=0 equation:

Simplifying z^{7}+ 2(z^{4}) + 4z = 0 Reorder the terms: 4z + 2z^{4}+ z^{7}= 0 Solving 4z + 2z^{4}+ z^{7}= 0 Solving for variable 'z'. Factor out the Greatest Common Factor (GCF), 'z'. z(4 + 2z^{3}+ z^{6}) = 0## Subproblem 1

Set the factor 'z' equal to zero and attempt to solve: Simplifying z = 0 Solving z = 0 Move all terms containing z to the left, all other terms to the right. Simplifying z = 0## Subproblem 2

Set the factor '(4 + 2z^{3}+ z^{6})' equal to zero and attempt to solve: Simplifying 4 + 2z^{3}+ z^{6}= 0 Solving 4 + 2z^{3}+ z^{6}= 0 Begin completing the square. Move the constant term to the right: Add '-4' to each side of the equation. 4 + 2z^{3}+ -4 + z^{6}= 0 + -4 Reorder the terms: 4 + -4 + 2z^{3}+ z^{6}= 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2z^{3}+ z^{6}= 0 + -4 2z^{3}+ z^{6}= 0 + -4 Combine like terms: 0 + -4 = -4 2z^{3}+ z^{6}= -4 The z term is 2z^{3}. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2z^{3}+ 1 + z^{6}= -4 + 1 Reorder the terms: 1 + 2z^{3}+ z^{6}= -4 + 1 Combine like terms: -4 + 1 = -3 1 + 2z^{3}+ z^{6}= -3 Factor a perfect square on the left side: (z^{3}+ 1)(z^{3}+ 1) = -3 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.## Solution

z = {0}

### See similar equations:

| z^7+2z^4+4z=0 | | 1/2(2x-6)=2x | | 3.46y-6.851=2.6y-1.35y | | 2+3x=5-2 | | 2/3(3x+18)=5x-9 | | x+2(3)=8 | | y=-4(-1)+5 | | y=-4(0)+5 | | (8x-12)(10-15x)=0 | | y=-4(1)+5 | | y=-4(2)+5 | | 63x^7=7x^5 | | 2(x-1)=3/5(10+5x) | | 12=4x-x | | -x^3+5x^2+10x-50=0 | | x-(x-0.2x)=43.46 | | 40t=55+3t | | 3*4x-6x=2*9x | | 200+3=1800 | | x^4-3x-4=0 | | 4-2y+3=-9 | | x^3+2*x^2-19x=0 | | (n+1)*8=24 | | (n-5)*2=6 | | (n+2)*2=8 | | 5x^8-4x^6-2x^4-4x^2+1=0 | | 3x-x^2-5=0 | | 12x-34=5x+2 | | -135-7x=10x | | -x^3+7x^2-11x=0 | | -y-6y= | | -6(-1)-2= | | 59-2x=16x+21 | | 4x*-15x-4=0 | | 7x-x^2=11 | | 83-5x=31x+23 | | 114-4x=14x+16 | | 12x^3=15 | | (5-x)(3x+6)=0 | | 12=13x+7y | | x^4-30x^2+221=0 | | 3-[-3+-7]=2 | | -x^2+7x-11=0 | | 5(x-2y)=2x+y | | 1.3=5-3x-4-4x | | 3-t=3t+2 | | 10x-17=14x-61 | | x^2-7x+15=9 | | x^2-8x+10=-2x+2 | | 6x^2-15x+8=0 | | 79-4x=8x-19 | | -3xy*2xy= | | 6x-9=-33-8x | | 230-3x=42+20 | | 11x+30=2x+300 | | 8x+5=3x+0 | | 152-10x=9x+19 | | 4x-5=72-7x | | 8(x+2)=4(x+10) | | a*8+6=3 | | x*x+7x=12 | | 7-9x=83-23x | | 148-2x=25x+19 | | (n-4)*6=12 | | (n+1)*9=27q |